Extensive Reading in Developing Language Competency for Indonesian EFL Learners Majoring in English - Syofia Delfi; Hamidah Yamat (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2017)
Extensive reading might develop EFL learners’English competency because in the process of reading, they keep on reading a lot of reading materials and immerse in the language use. This article is based on literature review for a study “ a Case Study on Two Indonesian Learners’ Extensive Reading in English Experiences towards Developing Reading Competency”. This article aims to describe how extensive reading contributes to English competency of EFL learners. The review shows that the contribution of extensive reading is in terms of the context of Indonesian EFL learners, learning language for Indonesian EFL learners, and characteristics and the benefit of extensive reading meet the Indonesian EFL Learners’ reading experiences. The more the learners read, the more they acquire the language, and the more they acquire the language, the more they develop their language competency. This process shows how extensive reading contributes to English competency. This review is expected to be meaningful for the study designed.